ANALISIS PENGARUH KOMPETENSI, BEBAN KERJA TERHADAP KINERJA GURU DENGAN MEDIASI KOMPENSASI (Studi pada Guru PAUD di Kecamatan Bululawang Kabupaten Malang) - Cecep Lili; Rahayu Puji Suci; Nasharuddin Mas (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2023)
The purpose of this study was to obtain empirical evidence of competence and workload in encouraging the performance of PAUD teachers, either directly or through compensation mediation. This type of research is quantitative with the SEM-SmartPLS method. Data were obtained through questionnaires which were distributed to 62 PAUD teachers in Bululawang District, Malang Regency. Empirical evidence shows that both competency and workload are capable of strongly driving increased PAUD teacher compensation and performance. Meanwhile, the mediation role of compensation is only able to strongly mediate the influence of competence on the performance of PAUD teachers. Meanwhile, the mediating role of compensation for the influence of workload on the performance of PAUD teachers in Bululawang District, Malang Regency, was weak